In vitro interactions of proton pump inhibitors and azoles against pathogenic fungi - Gao, Lujuan; Xia, Xuqiong; Gong, Xiao; Zhang, Heng; Sun, Yi (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Azole resistance has been increasingly reported and become an issue for clinical managements of invasive mycoses. New strategy with combination therapy arises as a valuable and promising alternative option. The aim of the present study is to investigate the in vitro combinational effect of proton pump inhibitors (PPIs) and azoles against pathogenic fungi. Methods In vitro interactions of PPIs including omeprazole (OME), lansoprazole (LAN), pantoprazole (PAN), and rabeprazole (RAB), and commonly used azoles including itraconazole (ITC), posaconazole (POS), voriconazole (VRC) and fluconazole (FLC), were investigated via broth microdilution chequerboard procedure adapted from the CLSI M27-A3 and M38-A2. A total of 67 clinically isolated strains, namely 27 strains of Aspergillus spp., 16 strains of Candida spp., and 24 strains of dematiaceous fungi, were studied. C. parapsilosis (ATCC 22019) and A. flavus (ATCC 204304) was included to ensure quality control. Results PPIs individually did not exert any significant antifungal activity. The combination of OME with ITC, POS, or VRC showed synergism against 77.6%, 86.6%, and 4% strains of tested pathogenic fungi, respectively, while synergism of OME/FLC was observed in 50% strains of Candida spp. Synergism between PAN and ITC, POS, or VRC was observed against 47.8%, 77.6% and 1.5% strains of tested fungi, respectively, while synergism of PNA/FLC was observed in 50% strains of Candida spp. Synergism of LAN with ITC, POS, or VRC was observed against 86.6%, 86.6%, and 3% of tested strains, respectively, while synergism of LAN/FLC was observed in 31.3% strains of Candida spp. Synergy of the combination of RAB with ITC, POS, or VRC was observed against 25.4%, 64.2%, and 4.5% of tested strains, respectively, while synergism of RAB/FLC was observed in 12.5% of Candida spp.. Among PPIs, synergism was least observed between RAB and triazoles, while among triazoles, synergism was least observed between VRC and PPIs. Among species, synergy was much more frequently observed in Aspergillus spp. and dematiaceous fungi as compared to Candida spp. Antagonism between PPIs with ITC or VRC was occasionally observed in Aspergillus spp. and dematiaceous fungi. It is notable that PPIs combined with azoles showed synergy against azole resistant A. fumigatus, and resulted in category change of susceptibility of ITC and POS against Candida spp. Discussion The results suggested that PPIs combined with azoles has the potential to enhance the susceptibilities of azoles against multiple pathogenic fungi and could be a promising strategy to overcome azole resistance issues. However, further investigations are warranted to study the combinational efficacy in more isolates and more species, to investigate the underlying mechanism of interaction and to evaluate the potential for concomitant use of these agents in human.